The Anglo-American synecdoche?: Thomas Jefferson’s British legacy 1800-1865 - O'Connor, Peter (Taylor and Francis, 2015)
This article is focused on one of the behemoths of American history, Thomas Jefferson. Unlike most studies, however, it removes the Virginian statesman from his familiar American context in order to illustrate his significance as a British icon. It considers the use of his image in British discourse between 1800 and 1865 to demonstrate the resonance of his name for British people of the period. In doing so it examines the uses of Jefferson’s image with reference to democracy and slavery to illustrate how the ambiguity and seeming contradictions in the deployment of his image are indicative of a broader debate in nineteenth century Britain about the meaning of the United States. Furthermore it demonstrates, through the use of Jefferson’s image, the steady but uneven process of disillusion with American politics and society among British reformers